Exploratory study of DeFi protocols: incentive and governance models - Tee, Wilson Teo Hong (Nanyang Technological University, 2023)
The emergence of blockchain technology has resulted in the development of various decentralized finance (DeFi) applications, transforming traditional financial systems by enabling peer-to-peer transactions, automated protocols, and increased financial inclusivity. This project dives into the analysis and exploration of various DeFi applications. Through comprehensive research of numerous DeFi applications, this study analyzes and compares the key features and incentives offered by various mechanisms. Furthermore, this project studies the corresponding governance model utilized by the various DeFi applications. An examination of the smart contract functionalities prevalent in DeFi applications is also presented, shedding light on any inconsistencies associated with these DeFi applications.